Errors in systems approaches. (1st January 2012) - Adams, Kevin MacG.; Hester, Patrick T.
Understanding and treating problems in complex systems, independent of the systems construct (i.e., socio-technical systems or socio-ecological systems), dictates the use of a formal systems approach. The systems approach may be methodological, a method, or a technique, but in each case it involves the imposition of order that ranges from the philosophical to the procedural. Independent of the philosophical construct or procedural rigor used in addressing the complex systems problem is the opportunity to commit a number of errors as part of the systems approach. This paper will discuss six classifications for problem solving errors that may be experienced during the application of a systems approach when understanding and treating complex systems problems.